On the importance of nuclear spin for dark matter detection - Bednyakov, Vadim A. (Array, 2008)
Summary: Weakly interacting massive particles (WIMPs) are among the main candidates for the relic dark matter (DM). The idea of the direct DM detection relies on elastic spin-dependent (SD) and spin-independent (SI) interaction of WIMPs with target nuclei. In this paper, the importance of the SD WIMP-nucleus interaction for reliable DM detection is argued. The effective low-energy minimal supersymmetric standard model (MSSM) is used for the calculation of the DM cross sections, provided the lightest neutralino is a WIMP. It is shown that the absolute lower bound for the rate of direct DM detection is due to the SD WIMP-nucleon interaction and a new-generation experiment aimed at detecting DM with sensitivity higher than 10-5 event/day/kg should have a non-zero-spin target to avoid missing of the DM signal